THE INFLUENCE OF REGIONAL FINANCIAL ACCOUNTING SYSTEM UNDERSTANDING AND INFORMATION TECHNOLOGY SYSTEM UTILIZATION ON INFORMATION QUALITY OF LOCAL GOVERNMENT FINANCIAL STATEMENTS WITH USER EXPERTISE AS MODERATION VARIABLE - Tenriwaru Tenriwaru; Ulya Aulia; Nurfadila Nurfadila (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2022)
Purpose – This study aims to determine the effect of understanding the regional financial accounting system and the use of information technology systems on the quality of information on local government financial statements with user expertise as a moderating variable Design/methodology/approach – The method used in this research is the analytical method, namely Moderated Regression Analysis (MRA) Findings – The study found that: (1) understanding of the regional financial accounting system has a positive but insignificant effect on the quality of information on regional government financial statements, (2) utilization of information technology systems has a positive and significant effect on the quality of information on regional government financial statements, (3) the effect of understanding the regional financial accounting system on the quality of financial statement information has a positive but insignificant effect with user expertise as a moderation variable, (4) utilization of information technology systems on information quality of financial statements has a positive and significant effect with user expertise as a moderation variable. Originality – The sample in this study was 30 SKPD in Makassar City who were selected through purposive sampling.